Ovarian organization and maturity stages of armored catfish Hypostomus strigaticeps (Siluriformes, Loriicaridae) - Takahashi, Erico Luis Hoshiba; Goitein, Roberto [UNESP]; Nakaghi, Laura Satiko Okada [UNESP] (My University, 2008)
This work studied the ovarian development of the armored catfish Hypostomus strigaticeps. Between July 2002 and June 2005, 332 females were collected monthly from the Corumbataí River, São Paulo State - Brazil. The ovaries were processed using routine histological techniques - paraffin inclusion and 5 μm thick sections stained in hematoxylin-eosin. Six types of oocytes were observed: Chromatin-nucleolus, Perinucleolar, Cortical-alveolus, Vitellogenic, Ripe and Atresic. Four maturity stages were created based on macroscopic and microscopic morphological observations, as well as on analysis of the gonadossomatic index (GSI): Rest, Maturation, Ripe and Spawned.
Maturidade do ovário no cascudo Hypostomus strigaticeps (Siluriformes, Loriicaridae)
Keywords: Fish; Gonad; Histology; Reproduction